*Z podanego wzoru wyznacz niewiadomą : y. Załóż, że wszystkie niewiadome są liczbami dodatnimi.

a). 2y - ab = c
b). b = -ay + dv
c). ay - c = 4ay - d

* Z podanego wzoru wyznacz niewiadomą : z . Załóż , że wszystkie niewiadome są liczbami dodatnimi.

a). z/a = b/z

1

Odpowiedzi

2010-04-12T01:20:17+02:00
*Z podanego wzoru wyznacz niewiadomą : y. Załóż, że wszystkie niewiadome są liczbami dodatnimi.

a). 2y - ab = c
2y=c+ab |:2
y=(c+ab)/2

b). b = -ay + dv
ay=dv-b |:a
y=(dv-b)/a

c). ay - c = 4ay - d
ay-4ay=c+d
y(a-4a)=c-d |:(a-4a)
y=(c-d/-3a


* Z podanego wzoru wyznacz niewiadomą : z . Załóż , że wszystkie niewiadome są liczbami dodatnimi.

a). z/a = b/z |*a
z=ab/z |*z
z2=ab
z=pierwiastek z ab
2 5 2